2011
DOI: 10.1007/s10719-011-9331-8
|View full text |Cite
|
Sign up to set email alerts
|

A structurally diversified linker enhances the immune response to a small carbohydrate hapten

Abstract: The tether employed to covalently attach β-mannan disaccharide glycoconjugates influences the specificity of rabbit antibodies that protect against Candida albicans. Two glycoconjugates containing (1 → 2)-β-mannan disaccharides linked to chicken serum albumin (CSA) either via a structurally uniform or via a stereodiversified spacer were prepared and evaluated in immunization trials in mice and rabbits. Immunization with conjugate vaccine possessing a structurally diversified linker induced higher IgG titers ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Interspecies (goat vs. mouse, rabbit vs. mouse) as well as mouse inter-strain differences in the ability to mount a glycan-specific antibody response to both native glycoproteins and synthetic glycoconjugates have been previously noted in the literature 17,3237 . One explanation for the observed differences between rabbits and mice could be a differentially tolerized immune repertoire due to differences between murine and rabbit milk oligosaccharide composition.…”
Section: Discussionmentioning
confidence: 90%
“…Interspecies (goat vs. mouse, rabbit vs. mouse) as well as mouse inter-strain differences in the ability to mount a glycan-specific antibody response to both native glycoproteins and synthetic glycoconjugates have been previously noted in the literature 17,3237 . One explanation for the observed differences between rabbits and mice could be a differentially tolerized immune repertoire due to differences between murine and rabbit milk oligosaccharide composition.…”
Section: Discussionmentioning
confidence: 90%
“…This was in sharp contrast to the poor immunogenicity of b-mannotriose-tetanus toxoid conjugate in mice (32,33,37). These observations prompted us to consider DC targeting as a means to enhance the antigenicity of the b-mannan-tetanus toxoid conjugate.…”
Section: Discussionmentioning
confidence: 99%
“…This vaccine induced high titers of b-mannan-specific Abs, in the range of 20,000-80,000, after only two injections using alum as adjuvant (32). Disappointingly, the same vaccine given to mice produced corresponding titers of 10,000 or lower, and these Ab levels were not significantly improved by more aggressive immunization protocols that employed powerful adjuvants such as CFA (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this competition between hapten and linkers, especially for conjugates utilising smaller oligosaccharides as the carbohydrate component, is going to effect the maturation of the immune response to the desired carbohydrate target. A recent paper by Lipinski et al [32] has introduced a novel alternative conjugation strategy, by utilising stereochemically variable linker molecules to suppress the immune response maturation to the linker moieties. The present study has therefore clearly confirmed and extended the potential of the inner core LPS as a vaccine candidate to combat disease caused by the significant veterinary pathogen M. haemolytica.…”
Section: Discussionmentioning
confidence: 99%